Water Scrubber and Zeolite Catalyst for Clean Syngas Production on Biomass Gasification of Bagasse in a Downdraft System (Jurnal Bahan Alam Terbarukan, 2022)
Biomass gasification is one solution that can overcome Indonesia's energy crisis. Indonesia is an agricultural country that has a lot of sources of biomass. This work was focused on clean syngas production with purifying process through a water scrubber and zeolite catalyst as a filter. The syngas was produced from bagasse gasification as solid waste from a sugar factory. The weight of bagasse feedstock was studied on 1000 g, 1500 g, 2000 g, 2500 g, and 3000 g. The influence of burning time and syngas composition were also studied on syngas production. The experiment result showed that the burning time of syngas is related to the amount of bagasse; the higher the bagasse, the longer the burning time. The syngas composition from the gasification process was investigated, and it was found that CO, CH4, and H2 were percentages of 9.294%, 1.348%, and 2.773%, respectively. The water scrubber and zeolite catalyst can affect the cleanness of the syngas.